When God and the Grind Collide: Religious Accommodations in the Post-Groff v. DeJoy Workplace - Grace Adams (UNC Test Journal, 2025)
This research examines the U.S. Supreme Court's 2023 decision Groff v. DeJoy and its impact on subsequent lower court rulings regarding religious accommodations in the workplace. The decision represents a significant shift by the Court in the interpretation of Title VII of the Civil Rights Act of 1964, by clarifying that employers denying an employee's accommodation must show a "substantial" rather than merely a "de minimis" (very small) cost to the organization. By analyzing recent lower court decisions applying this heightened standard, this research explores and synthesizes the evolving legal landscape and the various lower courts' interpretations of what, post-Groff, constitutes "undue hardship" on the conduct of employer's business' under Title VII exempting the employer from providing an accommodation. The findings show a growing emphasis post-Groff on employees' rights, particularly those of employees with minority beliefs (e.g., Sunni sect of Islam, Hebrew Nation, Seventh-Day Adventist) through the lower courts' more pragmatic, case-by-case review of the actual, practical costs of an accommodation within the unique context of a particular organization and consideration of all available alternative accommodations within that context. This research not only enhances the understanding of religious accommodations in employment law but also offers guidance for employers and courts navigating this complex area.